Crescimento e desenvolvimento de Plinia cauliflora de acordo com a intensidade luminosa em clima subtropical - Dotto, Marcelo (2015)
The jabuticaba fruit tree from classified in the Myrtaceae family and Plinia genre. There are about nine species of this fruit tree, that include as most important, Plinia trunciflora (jabuticaba de cabinho), naturally occurring in southwestern Paraná State, Brazil, P. cauliflora (jabuticaba Paulista or Jabuticaba Açu) and P. jaboticaba (Vell) (jabuticaba sabará), with all the over species producing fruit for the industry or fresh consumption. Nevertheless, there aren‟t commercial orchards with this culture, with highest yield part from extractive. This fact can be combined with lack of technical knowledge for the plants produce in the field. As these species are found in the forest, the first point is whether they can adapt to other light intensity conditions. The aim of this work was to identify the adaptive behavior of jabuticaba fruit seedling and tree when they were put in different light intensities and what this can be considered ideal for the growth, as well as, its influence in the leaves secondary compounds production. Two experiments were conducted, with the first involved with the study of the seedlings and the second with plants in the field. The work was carried out at Universidade Tecnológica Federal do Paraná – Câmpus Dois Vizinhos, Paraná State - Brazil. The experimental design was a completely randomized and a block design with four treatments and four replications of 10 seedlings or two plants per plot, according to nursery or orchard conditions, respectively. The treatments were base according to the light intensity. The treatments used were, 1 - full sun, similar the orchard condition, with 0% shading; 2 - side cover with shade cloth and top with transparent plastic, representing a gap forest condition; 3 - side and top cover with shade cloth, representing stage where the forest canopy is closing, focusing only indirect sunlight; 4 - side and top cover with shade cloth, simulating a closed canopy condition, with PPD (photon flux density) of 10% (90% shading); 5 - side and top cover with shade cloth, simulating a more open canopy condition with PPD 65% (35% shading). The growth and development seedling and plant characteristics were evaluated once by month, as also, during time part in the plants the secondary metabolites leaves, soil activity microbiological and the fresh and dry matter root and shoot and, root length from seedlings. For the growth and development of jabuticaba Açú Paulista seedling recommend to use of side cover with shade cloth and top with transparent plastic, representing a gap forest condition. In orchard, for the growth and development of plants jabuticaba Híbrida tree it was recommended the use of side and top cover with shade cloth of some type. For production of secondary metabolites of leaves, the plant must to be full sunlight condition orchard.